Factors affecting adoption intensity of climate change adaptation practices: A case of smallholder rice producers in Chitwan, Nepal - Upendram, Sreedhar; Regmi, Hari P.; Cho, Seong-Hoon; Mingie, James C.; Clark, Christopher D. (Frontiers in Sustainable Food Systems, 2023)
This study examines how adoption intensity for climate change adaptation practices related to rice production (i.e., improved varieties, irrigation practices, direct seeded rice, integrated pest management, and adjustment in crop calendar) influences access to Extension services, training, weather-related information, and membership in farmer groups or cooperatives (referred to as “institutional factors”). We use survey data collected from 359 rice producers in the Chitwan district of Nepal in 2019. The results indicate: 1) access to institutional factors significantly enhance the likelihood of adoption of more climate change adaptation practices, 2) high intensity climate change adaptation practice measured by the adoption of three, four, and five climate change adaptation practices significantly increases with access to institutional factors, 3) intensity of adoption of climate change adaptation practices is reduced with greater adaptation alternatives available to rice producers, and 4) lack of information and technical knowledge are the most important reasons for non-adoption of climate change adaptation practices by rice producers. The results are valuable for policy makers and planners to prioritize training opportunities and allocate scarce resources to enhance climate change adaptation and improve sustainability of rice production practices.